ZAKAT PERDAGANGAN DENGAN MODAL HUTANG DI UD. LIMA LAPAN SAMPANG - Abdurrahman Ghozali (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
Zakat trade or commerce is issued zakat on property ownership that is destined for sale, zakat is imposed on trade which arranged either individually or in combinations (UD, PT, cooperatives, etc.). Almost all scholars agree that the trade was once certain conditions are met should be issued zakat, namely: first, real property owned as of the sale and purchase, marriage, probate, khul'a (ransom), the spoils of war, received grants, and efforts kosher, and other such. Second, the property was owned intended for trading. If not, then the property is not included commercial property. A treasure in the hands of others (accounts receivable), and still have hopes that the property will be returned to the hands, when they are obliged to haul menzakatinya, because the asset's like money in the bank you tube or elsewhere. But if you have no hope of getting these treasures such as the debtor is bankrupt, so in this case you are not obliged menzakatinya. Such authentic opinion among the scholars opinion.